The Importance of Positive Youth Development Attributes to Life Satisfaction and Hopelessness in Mainland Chinese Adolescents - Zhou, Zheng; Shek, Daniel T. L.; Zhu, Xiaoqin (Frontiers in Psychology, 2020)
In contrast to mainstream theories focusing on adolescent developmental deficits, the positive youth development (PYD) approach highlights adolescent developmental plasticity and potentials. There are rich empirical research and review studies showing that PYD attributes promote adolescent well-being. However, the existing literature shows several limitations. First, while there are many Western studies, Chinese studies are sparse, particularly studies in mainland China. Second, most PYD studies are cross-sectional studies with data collected at one single time point. Third, researchers in different Chinese contexts seldom employed validated Chinese scales assessing different domains of PYD attributes. Fourth, few studies have examined the relationships between PYD attributes (measures of eudaimonic well-being) and life satisfaction (measure of hedonic well-being) and hopelessness (measure of negative well-being) in a single study. Finally, the role of life satisfaction or hopelessness as a mediator of the relationship between PYD attributes and psychological well-being is unclear. To explore the importance of PYD attributes to Chinese adolescent psychological well-being, we conducted a longitudinal study with two waves of data collected from junior high school students in mainland China (N = 2,648). At both times, validated measures of PYD attributes, life satisfaction, and hopelessness were employed. Results showed that PYD attributes concurrently and longitudinally predicted life satisfaction and hopelessness with small effect sizes. Cross-lagged panel analyses showed that while Wave 2 life satisfaction did not serve as a mediator of the relationship between Wave 1 PYD attributes and Wave 2 hopelessness, Wave 2 hopelessness served as a mediator of the link from Wave 1 PYD attributes to Wave 2 life satisfaction. In view of the paucity of research findings in this area, the present findings clarify the association between PYD attributes and hedonic well-being (indexed by life satisfaction) and negative psychological well-being (indexed by hopelessness) in Chinese adolescents.